Prematurity Modifies the Risk of Long-term Neurodevelopmental Impairments After Invasive Group B Streptococcus Infections During Infancy in Denmark and the Netherlands. (3rd November 2021) - Horváth-Puhó, Erzsébet; Snoek, Linde; van Kassel, Merel N; Gonçalves, Bronner P; Chandna, Jaya; Procter, Simon R; van de Beek, Diederik; de Gier, Brechje; van der Ende, Arie; Sørensen, Henrik T; Lawn, Joy E; Bijlsma, Merijn W; et al.
Abstract: Background: Preterm birth and neonatal infections are both associated with mortality and long-term neurodevelopmental impairments (NDIs). We examined whether the effect of invasive group B Streptococcus disease (iGBS) on mortality and long-term NDI differs for preterm and term infants, and whether co-occurrence of iGBS and prematurity leads to worse outcome. Methods: Nationwide cohort studies of children with a history of iGBS were conducted using Danish and Dutch medical databases. Comparison cohorts of children without iGBS were matched on birth year/month, sex, and gestational age. Effects of iGBS on all-cause mortality and NDI were analyzed using Cox proportional hazards and logistic regression. Effect modification by prematurity was evaluated on additive and multiplicative scales. Results: We identified 487 preterm and 1642 term children with a history of iGBS and 21 172 matched comparators. Dutch preterm children exposed to iGBS had the highest mortality rate by 3 months of age (671/1000 [95% CI, 412–929/1000] person-years). Approximately 30% of this mortality rate could be due to the common effect of iGBS and prematurity. Preterm children with iGBS had the highest NDI risk (8.8% in Denmark, 9.0% in the Netherlands). Of this NDI risk 36% (Denmark) and 60% (the Netherlands) might be due to the combined effect of iGBS and prematurity. Conclusions: Prematurity is associated with iGBS development. Our study shows that it also negatively impacts outcomes of children who survive iGBS. Preterm infants would benefit from additional approaches to prevent maternal GBS colonization, as this decreases risk of both preterm birth and iGBS.